Student Teachers' Views on the Skills of Creating Hyper-content Modules for Prospective Early Childhood Teachers - Andini Linarsih; Dian Miranda; Marmawi Marmawi; Lukmanulhakim Lukmanulhakim; Desni Yuniarni (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2022)
Technology integration in the classroom is indispensably important to enhance the transfer of information in the class. One of the technology-integrated media that can train student-teachers ‘creativity and their computitional thinking is e-module hypercontent. This study investigates the student teacher of early childhood education’ voices regarding the benefits of e-module hypercontent after they completed their e-module hyperconten training. The data was collected through a questionaire. The result indicates that 60% of participants felt that the training material this time was very much needed for future career development, and they felt that the material provided was easy so that their skills in making PAUD learning media in the form of hypercontent e-modules increased.